2021
DOI: 10.5194/acp-21-2383-2021
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of non-methane volatile organic compounds from combustion of domestic fuels in Delhi, India

Abstract: Abstract. Twenty-nine different fuel types used in residential dwellings in northern India were collected from across Delhi (76 samples in total). Emission factors of a wide range of non-methane volatile organic compounds (NMVOCs) (192 compounds in total) were measured during controlled burning experiments using dual-channel gas chromatography with flame ionisation detection (DC-GC-FID), two-dimensional gas chromatography (GC × GC-FID), proton-transfer-reaction time-of-flight mass spectrometry (PTR-ToF-MS) and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 141 publications
1
21
0
Order By: Relevance
“…Whilst SPE samples for these compounds remained semiquantitative, due to breakthrough, the detection of high emissions of phenolics and furanics in the gas phase from burning was in line with recently published studies (Hatch et al, 2015;Stockwell et al, 2015;Koss et al, 2018). Relatively low levels of total quantified material within the aerosol phase was in line with current literature (Jen et al, 2019), but meant that this analysis was not entirely reflective of the organic fraction for complex samples.…”
Section: Compositionsupporting
confidence: 81%
See 1 more Smart Citation
“…Whilst SPE samples for these compounds remained semiquantitative, due to breakthrough, the detection of high emissions of phenolics and furanics in the gas phase from burning was in line with recently published studies (Hatch et al, 2015;Stockwell et al, 2015;Koss et al, 2018). Relatively low levels of total quantified material within the aerosol phase was in line with current literature (Jen et al, 2019), but meant that this analysis was not entirely reflective of the organic fraction for complex samples.…”
Section: Compositionsupporting
confidence: 81%
“…VOCs react to form ozone and secondary organic aerosol (SOA). Intermediate-volatility and semi-volatile organic compounds (I/SVOCs) are also a significant emission from biomass burning (Stockwell et al, 2015;Koss et al, 2018). I/SVOCs are an important class of air pollutant due to their contribution to aerosol formation (Bruns et al, 2016;Lu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There have been several recent studies focused on understanding VOC emissions from sources specific to Delhi. Stewart et al (2021b) studied the types of intermediatevolatility and semi-volatile gases released from solid fuels in Delhi to better understand their potential impact on air quality, and Stewart et al (2021c) produced highly speciated nonmethane VOC (NMVOC) emission factors from a range of solid fuel combustion sources characteristic to Delhi, which were used by Stewart et al (2021d) in regional policy models and global chemical transport models. Stewart et al (2021e) found that fuel wood, crop residue, cow dung cake, and municipal solid waste burning were shown to be 30, 90, 120, and 230 times more reactive with the OH radical, which can lead to O 3 formation, than liquified petroleum gas (LPG), and may be one the factors for the high O 3 levels, and overall poor air quality, observed.…”
Section: Introductionmentioning
confidence: 99%
“…According to Stewart et al . (2021), manure cake had a higher emissions factor than fuelwood and liquefied petroleum gas, suggesting that the contribution to environmental pollution from burning manure cake is substantial.…”
Section: Social Cultural and Economic Determinants Of Nitrogen Pollut...mentioning
confidence: 99%
“…The manure is mixed with crop residue and sun-dried in the form of mid-sized pellets (Sfez et al, 2017;Prasad et al, 2019). According to Stewart et al (2021), manure cake had a higher emissions factor than fuelwood and liquefied petroleum gas, suggesting that the contribution to environmental pollution from burning manure cake is substantial.…”
Section: Economic Factorsmentioning
confidence: 99%